24HABPM IN THE LONG TERM FOLLOW UP OF RENAL TRANSPLANT PATIENTS: FOCUS ON AN UNMET CLINICAL NEED. (June 2018) - Mallamaci, F.; Tripepi, R.; D'Arrigo, G.; Porto, G.; Versace, M.C.; Marino, C.; Sanguedolce, M.C.; Tripepi, G.; Zoccali, C.
Abstract: Objective: Non-dipping is much frequent in renal transplant patients and over 50% of these patients have nocturnal hypertension. Hypertension misclassification by office BP is quite common in this population and this phenomenon may alter therapeutic decisions in clinical practice. However, 24hABPM is not formally recommended by the current renal transplantation guidelines and it is rarely applied in most transplant centres. Design and method: We performed a longitudinal study in 260 clinically stable renal transplant patients. All patients had at least one 24 h ABPM recording, 199 had two, 143 had three, 74 pts had four and 109 pts had>four ABPMs. Overall, 785 paired office and 24 h ABPM measurements over a 3.9 years median follow-up were available in the whole cohort. Data analysis was performed by the Generalized Estimating Equations (GEE) and the kappa statistics. Results: At baseline visit on average both office (132 ± 16/78 ± 10 mmHg) and 24hABPM (125 ± 12/77 ± 9 mmHg) were controlled fairly well but as much as the 74% of patients had nocturnal hypertension by the ESH criterion (> = 120/70 mmHg). In an analysis by the General Estimating Equations, office BP (P = 0.97) and 24hABPM (P = 0.63) remained quite stable over follow up as it did the frequency of nocturnal hypertension (P = 0.64) which was 77% at the last observation. However, the global agreement of the two metrics for the classification of hypertension was very poor (k statistics 20%). In as much as 193 visits (25% of all visits) where office BP indicated the need of antihypertensive therapy institution or modification (BP> = 140/90 mmHg) synchronous 24hABPM was actually normal (<130/80 mmHg) while in additional 124 visits (16% of all visits) 24hABPM was in the hypertensive range while office BP was in the normotensive range. Overall, in 40% of visits office BP provided misleading therapeutic indications. Conclusions: Hypertension misclassification by office BP is a pervasive phenomenon in stable renal transplant patients on long term follow up. Office BP may lead to inappropriate therapeutic decisions in 40% of follow up visits in these patients. Periodic application of 24hABPM for the management of renal transplant patients should be formally recommended in this population.